PET/CT in Prostate Cancer - Cook, Gary (Springer International Publishing : Imprint: Springer, 2017)
This pocket book explains the significant and well-documented impact that PET/CT can have on the management of prostate cancer through the provision of high-quality evidence regarding function and structure. Up-to-date information is supplied on the relevance of PET/CT to diagnosis, treatment planning, and therapy, including the emerging role of PET/CT with PSMA. Readers will also find clear explanation of the relation of the clinical and pathological background to imaging and the value of PET/CT compared with conventional radiological imaging. The book will be an excellent asset for referring clinicians, nuclear medicine/radiology physicians, radiographers/technologists, and nurses who routinely work in nuclear medicine and participate in multidisciplinary meetings. It is published within the Springer series Clinicians' Guides to Radionuclide Hybrid Imaging, which presents contributions from professionals worldwide who share a common purpose in promoting nuclear medicine as an important imaging specialty for the diagnosis and management of oncological and non-oncological conditions.
Keywords: Medicine.; Nuclear medicine.; Oncology.; elektronické knihy; electronic books